Deliver us [videorecording (DVD)] - Kimmel, Jaune; Kretschmann, Thomas, 1962-; Kunz, Lee Roy; Kunz, Lee Roy; Leht, Marko; Luhse, Lena Barbara; Kunz, Kane (Magnolia Home Entertainment, 2023)
When a nun in a remote convent claims immaculate conception, the Vatican sends a team of priests to investigate, concerned about an ancient prophecy that a woman will give birth to twin boys: one the Messiah, the other the Anti-Christ.